Islam, revival, and reform : redefining tradition for the twenty-first century : essays inspired by John O. Voll - DeLong-Bas, Natana J. (Modern intellectual and political history of the Middle East., 2022)
"This edited volume examines the 18th century roots of the often-troubled marriage of politics and religion in the Muslim world and their impact on contemporary developments, including the globalization of Islam in the 21st century"--